Exploring campus diversity : case studies and exercises - Thompson, Sherwood; Parry, Pam (Rowman & Littlefield, 2018)
"This book examines challenges of expanding diversity and equity on college and university campuses in America. Each chapter communicates a problematic diversity situation, framing and understanding the problem, and a list of discussion questions aimed at developing strategies help guide the reader from the theoretical to the practical"--